English Beyond Objectivity: The Problem of the Thinker in the Context of Scientific Models - Menin, Boris (European Journal of Science, Innovation and Technology, 2024)
The subjective experience of the "thinker" and the objective reality represented in scientific or technical models are in a complex interaction. The "objectivity" of scientific progress is accompanied by an inevitable subjectivity in the choice of a model in physics. This article examines the "thinker problem", which reflects the mental picture of the thinker, conditioned by his intuition, knowledge and experience and influencing his perception of reality and the models he constructs. The article substantiates the important role of the International System of Units (SI) used by the thinker in constructing a model. The Abelian structure of the SI and the finite amount of information contained in it dictate the limits of achievable accuracy in scientific research. However, the article argues that the thinker's freedom of choice in formulating a model is a necessary component of scientific progress. The article analyzes the contradictory interaction between this freedom and the desire to discover fundamental physical laws, while acknowledging the existence of limits to the accuracy of experimental measurements and the current lack of a generally accepted criterion for choosing the "most plausible" model. The article emphasizes the complex relationship between constructed models, experimental results and the philosophical position of the thinker, which obliges him to adhere to a strict methodological approach in scientific research.